PENGARUH LEVERAGE, PROFITABILITAS, DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK (Studi Kasus Perusahaan Pertambangan Yang Terdaftar Di Index Saham Syariah Indonesia (ISSI) tahun 2016-2021) - Shinta Lerlianti Putri; Ilham Illahi (CV. Adiba Aisha Amira, 2023)
This study aims to determine whether there is an effect of leverage, profitability, and audit quality on tax avoidance. Tax avoidance in this study is calculated by CETR (Cash Effective Tax Ratio). The data used is secondary data in the form of financial statements of mining companies listed on the Sahan Syariah Indonesia Index (ISSI) for the 2016-2021 period. Sampling technique with purposive sampling and data was analyzed using multiple linear regression analysis with the help of SPSS 26 software. The sample that met the criteria amounted to 22 companies with 6 years of observation. The results showed that leverage and audit quality had a significant negative effect on tax avoidance while profitability had no effect on tax avoidance.